Fermentacao de 26-deoxilaidlomicina por Streptomyces sp. Ar386 - Ujikawa, K. [UNESP] (My University, 1996)
In a previous work a strain of microorganism was isolated in Araraquara region, SP, Brazil, and characterized as being Streptomyces sp. Ar386, producer of 26-deoxylaidlomycin and of more three polietheric antibiotics. In this paper there are presented studies about fermentation characteristics of the antibiotic performed in incubator agitator utilizing various cultivation technics and media. A medium containing part of energy source as free sugar and part as amilaceous material presented the best result. As the Streptomyces sp. Ar386 produced few spores, it was necessary special care to provide sufficient quantity of microorganisms in inoculation. The biosynthesis of antibiotics intensified between the forth and seventh day. The yields varied from 8 to 443 mg of antibiotic complex per litre of medium. As a polyether antibiotic it may be used as anticoccidal agent in poultry and as growth promoters in cattle and swine.
Fermentation of 26-deoxylaidlomycin by Streptomyces sp. Ar386
Keywords: 26-deoxylaidlomycin; antibiotic; Brazil; coccidiostatic; fermentation; Streptomyces sp. Ar386; 26 deoxylaidlomycin; antibiotic agent; biosynthesis; drug manufacture; nonhuman; streptomyces